COMPARATIVE RESEARCH OF CONSUMER PURCHASE INTENTION TOWARDS ORIGINAL AND COUNTERFEIT PRODUCT OF NIKE SHOES IN MANADO - Mangundap, Beauty C.A; Massie, James D.D; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Counterfeit products have spreads worldwide, and Indonesia is no exception. Nowadays, the Original and Counterfeit Product has a similarity appearances and can make consumer difficult to distinguish the difference between Original and Counterfeit product, especially for footwear product. Nike shoes is one of 3 most popular footwear product that has been counterfeiting and There are so many users ofÂ  Nike Shoes in Indonesia, especially in Manado.This study is aim to know the significant different between Original and Counterfeits product of Nike Shoes Based on Consumer Purchase Intention. The method in this study is quantitative method by used independent sample t-test as the analyzing tools. Samples used in this research are 100 respondents and gathered from questionnaires. The data is analyzed by using SPSS Software. The result show that there is significant difference between Original and Counterfeit product based on the variables of Purchase intention, which is Product Quality, Price, Personal Appearance, Social Influence, and Brand Image. The research recommends for consumer that have intention to buy Nike Original and Counterfeit to choose product based on the variables of Purchase Intention.Keywords : purchase intention, product, originality, counterfeit, product quality, price, personal appearance, social influence, brand image